EVI1, a target gene for amplification at 3q26, antagonizes transforming growth factor‐β‐mediated growth inhibition in hepatocellular carcinoma. Issue 7 (5th June 2015) - Yasui, Kohichiroh; Konishi, Chika; Gen, Yasuyuki; Endo, Mio; Dohi, Osamu; Tomie, Akira; Kitaichi, Tomoko; Yamada, Nobuhisa; Iwai, Naoto; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; et al.
<x xml:space="preserve">Abstract</x> EVI1 (ecotropic viral integration site 1) is one of the most aggressive oncogenes associated with myeloid leukemia. We investigated DNA copy number aberrations in human hepatocellular carcinoma (HCC) cell lines using a high‐density oligonucleotide microarray. We found that a novel amplification at the chromosomal region 3q26 occurs in the HCC cell line JHH‐1, and that MECOM (MDS1 and EVI1 complex locus), which lies within the 3q26 region, was amplified. Quantitative PCR analysis of the three transcripts transcribed from MECOM indicated that only EVI1, but not the fusion transcript MDS1–EVI1 or MDS1, was overexpressed in JHH‐1 cells and was significantly upregulated in 22 (61%) of 36 primary HCC tumors when compared with their non‐tumorous counterparts. A copy number gain of EVI1 was observed in 24 (36%) of 66 primary HCC tumors. High EVI1 expression was significantly associated with larger tumor size and higher level of des‐γ‐carboxy prothrombin, a tumor marker for HCC. Knockdown of EVI1 resulted in increased induction of the cyclin‐dependent kinase inhibitor p15INK4B by transforming growth factor (TGF)‐β and decreased expression of c‐Myc, cyclin D1, and phosphorylated Rb in TGF‐β‐treated cells. Consequently, knockdown of EVI1 led to reduced DNA synthesis and cell viability. Collectively, our results suggest that EVI1 is a probable target gene that acts as a driving force for the amplification at 3q26 in HCC and that the oncoprotein EVI1 antagonizes TGF‐β‐mediated growth inhibition of HCC cells.